Leptospira interrogans outer membrane protein LipL21 is a potent inhibitor of neutrophil myeloperoxidase. Issue 1 (31st December 2018) - Vieira, Monica L.; Teixeira, Aline F.; Pidde, Giselle; Ching, Ana T. C.; Tambourgi, Denise V.; Nascimento, Ana Lucia T. O.; Herwald, Heiko
ABSTRACT: Leptospirosis is a widespread zoonotic and neglected infectious disease of human and veterinary concern that is caused by pathogenic Leptospira species. After entrance in the host, pathogenic leptospires evade the host natural defense mechanisms in order to propagate and disseminate to multiple organs. Myeloperoxidase is an enzyme stored in neutrophils azurophilic granules, and is released upon neutrophil activation to produce mainly hypochlorous acid, a strong oxidant and potent antimicrobial agent. In the present investigation, we studied the modulation of myeloperoxidase activity by L. interrogans serovar Copenhageni. We show that leptospires and their culture supernatants are able to inhibit both peroxidase and chlorination activities of myeloperoxidase, without interfering with neutrophil degranulation. By leptospiral outer membrane protein extraction and fractionation, we identified the proteins LipL21 and LipL45 as myeloperoxidase inhibitors, constituting new Leptospira virulence factors. Accordingly, we propose a function for the protein LipL21, one of the most expressed leptospiral outer membrane proteins. Our results show a novel innate immune evasion mechanism by which leptospires interfere with the host response in order to cope with the host oxidative stress and efficiently achieve dissemination and colonization.